2017
DOI: 10.1182/blood-2017-06-787200
|View full text |Cite
|
Sign up to set email alerts
|

Frontline brentuximab vedotin in combination with dacarbazine or bendamustine in patients aged ≥60 years with HL

Abstract: Patients aged ≥60 years with treatment-naive Hodgkin lymphoma (HL) have few treatment options and inferior survival due to treatment-related toxicities and comorbidities. This phase 2, nonrandomized, open-label study evaluated brentuximab vedotin (BV) monotherapy (results previously reported), BV plus dacarbazine (DTIC), and BV plus bendamustine. Patients had classical HL and were ineligible for or declined frontline chemotherapy. Twenty-two patients received 1.8 mg/kg BV and 375 mg/m DTIC for up to 12 cycles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 28 publications
0
72
0
2
Order By: Relevance
“…We confirm in our real‐life experience elderly HL patients are characterized by less favourable outcome if compared to published data about younger patients. Our study has some limitations, above all it is a retrospective analysis of a small sample size, even if comparable to previously published experiences . We recommend baseline CGA and suggest ABVD could represent a useful option with curative intent for a group of fit patients ≤70 years old .…”
Section: Patient's Characteristicsmentioning
confidence: 56%
See 1 more Smart Citation
“…We confirm in our real‐life experience elderly HL patients are characterized by less favourable outcome if compared to published data about younger patients. Our study has some limitations, above all it is a retrospective analysis of a small sample size, even if comparable to previously published experiences . We recommend baseline CGA and suggest ABVD could represent a useful option with curative intent for a group of fit patients ≤70 years old .…”
Section: Patient's Characteristicsmentioning
confidence: 56%
“…BV was associated with bendamustine or dacarbazine in 42 older HL patients ineligible for ABVD; bendamustine arm was interrupted because of toxicity. BV plus dacarbazine arm achieved a CR rate of 62% with a median PFS of 17.9 months . In a recent trial, BV was associated with cyclophosphamide, doxorubicin and prednisone (B‐CAP); 1‐year PFS was 73.9%, grade 4 leukopenia and grade 3 peripheral neuropathy were observed in 41% and 20% of cases, respectively .…”
Section: Patient's Characteristicsmentioning
confidence: 99%
“…A total of 65% of the patients experienced adverse events and two of the patients (10%) died due to treatment‐induced toxicity, resulting in discontinuation of the brentuximab vedotin plus bendamustin arm of the study. The combination of brentuximab vedotin with dacarbazine was better tolerated, however the CR rate was only 62% and the median PFS was 17·9 months (Friedberg et al , ).…”
Section: Frail Patientsmentioning
confidence: 99%
“…In accordance with previous results using ABVD, this suggests that AVD might not be the ideal chemotherapy‐backbone for simultaneous combination to novel substances in older HL patients (Böll et al , ; Evens et al , ). The combination of BV with bendamustine or dacarbazine in older HL patients resulted in premature termination of the bendamustine combination due to unexpected toxicity and no indication of superior efficacy with BV plus dacarbazine (Friedberg et al , ). Evens et al () recently reported the results of a multicentre phase II study of BV sequentially before and after six cycles AVD for older advanced stage HL patients, including 48 patients with a median age of 69 years and a median CIRS‐G score of 7.…”
Section: Discussionmentioning
confidence: 99%